(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Indian banks are using AI-powered chatbots to provide better customer service through real time communication and problem-solving. This research study aims to compare customer intent in using chatbot services offered by private and public sector banks. Additionally, the study investigates the significant factors that explain customer behavioral intent to use AI-powered chatbot services. The paper collected primary data from Indian public and private sector bank customers in Delhi-NCR through Google form links, Instagram, and Facebook. The Unified Theory of Acceptance and Use of Technology (UTAUT) 2 was assessed, and statistical tools such as paired sample t-tests and multiple regression were used to test the hypotheses. The results of the multiple regression analysis showed that hedonic motivation plays a significant role in understanding the intent of public sector customers to use chatbots, while habit plays a significant role for private bank customers. The authors observed a significant difference between public sector bank customers and private bank customers in terms of behavioral intent to use chatbot services, concluding that private bank customers are more intent on using chatbots compared to public sector customers.